Secondary Cytoreduction and Carboplatin Hyperthermic Intraperitoneal Chemotherapy for Platinum-Sensitive Recurrent Ovarian Cancer: An MSK Team Ovary Phase II Study. Issue 23 (10th August 2021) - Zivanovic, Oliver; Chi, Dennis S.; Zhou, Qin; Iasonos, Alexia; Konner, Jason A.; Makker, Vicky; Grisham, Rachel N.; Brown, Amy K.; Nerenstone, Stacy; Diaz, John P.; Schroeder, Eric D.; Langstraat, Carrie L.; et al.
Abstract : PURPOSE: The purpose of this phase II study was to evaluate hyperthermic intraperitoneal chemotherapy (HIPEC) with carboplatin for recurrent ovarian cancer during secondary cytoreductive surgery. MATERIALS AND METHODS: Patients were intraoperatively randomly assigned to carboplatin HIPEC (800 mg/m 2 for 90 minutes) or no HIPEC, followed by five or six cycles of postoperative IV carboplatin-based chemotherapy, respectively. Based on a binomial single-stage pick-the-winner design, an arm was considered winner if ≥ 17 of 49 patients were without disease progression at 24 months post-surgery. Secondary objectives included postoperative toxicity and HIPEC pharmacokinetics. RESULTS: Of 98 patients, 49 (50%) received HIPEC. Complete gross resection was achieved in 82% of the HIPEC patients and 94% of the standard-arm patients. Bowel resection was performed in 37% of patients in the HIPEC arm compared with 65% in the standard ( P = .008). There was no perioperative mortality and no difference in use of ostomies, length of stay, or postoperative toxicity. At 24 months, eight patients (16.3%; 1-sided 90% CI, 9.7 to 100) were without progression or death in the HIPEC arm and 12 (24.5%; 1-sided 90% CI, 16.5 to 100) in the standard arm. With a medium follow-up of 39.5 months, 82 patients progressed and 37 died. The median progression-free survival in the HIPEC and standard arms were 12.3 and 15.7 months, respectively (hazard ratio, 1.54; 95% CI, 1 to 2.37; P = .05). There was no significant difference in median overall survival (52.5 v 59.7 months, respectively; hazard ratio, 1.39; 95% CI, 0.73 to 2.67; P = .31). These analyses were exploratory. CONCLUSION: HIPEC with carboplatin was well tolerated but did not result in superior clinical outcomes. This study does not support the use of HIPEC with carboplatin during secondary cytoreductive surgery for platinum-sensitive recurrent ovarian cancer.